The influence of Kahoot-based TBLT in improving the critical reading skills in higher education - Wibowo, Amiruddin Hadi; Munir, Ahmad; Suhartono (Edelweiss Applied Science and Technology, 2024)
This study aimed to assess the effectiveness of Task-based language Teaching (TBLT) approach through Kahoot in improving EFL students’ critical reading skills. The study used a quasi-experimental method with a pre-experiment design involving a pre and post-test for one group. The research was conducted with 70 students (15 males and 65 females) from the Department of English Education at a Private University in Indonesia. The Kahoot-based TBLT approach was used to assess students’ critical reading skills. The data were analyzed utilizing paired t-tests and N-gain to determine the effectiveness. The result showed a significant improvement in critical reading skills from the pre-test to the post-test after using the Kahoot-based TBLT model. the findings indicate that the Kahoot-based TBLT model is a successful approach in improving students’ critical reading skills. Therefore, it can be concluded that Kahoot-based TBLT is effective in improving EFL students’ critical skill. Future research recommends the usage of Kahoot-based TBLT by educators to increase academic success in English language learning for higher education students.